(untitled) (Docentes 2.0 Journal, 2020)
Most of the computer software development projects do not finish in the estimated time or cost, in addition the end user is not completely satisfied with the delivered product, therefore the objective was to expose in a documentary way what are the factors of success and failure of the designs, as well as how these factors relate to the end user and the impact on their development. As a source of information, 15 documents were analyzed, reports published by The Standish Group from 1994 to 2015, as an organization in charge of these studies, in addition to the “Chaos Report” report, which provided a global view of statistics on computer processes. The method of compiling existing studies allowed an analysis of documented causes of failure; Later, he was able to classify causes related to the end user or customer, standing out: lack of adequate participation, lack of involvement, lack of feedback, users with poor communication skills, unrealistic user expectations, lack of final expectation management, incomplete requirements, lack of attitudes and rejection of change. As a final contribution, he presented a procedure through teaching accompaniment as a tool to solve problems through practical teaching in projects carried out by students of an IES for the final client, taking into account the proposed recommendations and the factors that originate the failure of the plans, ensuring that the end user is part of the success.